Application of a high entropy Prussian blue material in the preparation of aqueous nickel-ion batteries
By using high-entropy Prussian blue material as the positive electrode material in aqueous nickel-ion batteries, the problem of poor cycling stability of Mn-PBA in batteries is solved, and the improvement of high-nickel ion diffusion kinetics and electrochemical performance is achieved, and there is broad application prospect.
Patent Information
- Application Number
- CN202411905503.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-12-19
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
AI Technical Summary
The existing Mn-PBA as a cathode material shows high polarization and poor cycle stability in aqueous nickel-ion batteries, mainly due to poor conductivity, side reaction with the electrolyte, phase change, and dissolution of Mn elements.
High-entropy Prussian blue material is used as the cathode material. By applying a high-entropy strategy in the Prussian blue analog of Mn, the spin state of Mn is reduced, the crystal structure is stabilized, and the J-T distortion activity is inhibited, thereby improving nickel ion diffusion kinetics and comprehensive electrochemical properties.
After 1000 cycles, the retention rate of high entropy PBA positive electrode material exceeds 70%, showing a high nickel ion diffusion coefficient and high discharge capacity, and is environmentally friendly and low-cost.
Smart Images

Figure CN119764609A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of three-dimensional metal frame materials, and specifically relates to the application of a high-entropy Prussian blue material in the preparation of aqueous nickel-ion batteries. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] The overexploitation of fossil fuels and serious environmental pollution problems have prompted researchers to develop new energy storage devices. Lithium-ion batteries (LIBs) dominate the energy storage market due to their high energy density and long cycle life, but the development of LIBs is limited by many factors, such as the use of toxic and flammable electrolytes and the lack of lithium resources. In order to solve the above problems, various charge carriers (Na2+, Na2+, and Li2+) have been comprehensively studied. + , K + Mg 2+ 、Al 3+ , Ca 2+ 、H3O + and NH4 + However, there are few reports on energy storage using transition metal ions.
[0004] Among the candidates, aqueous nickel-ion batteries with transition metal ions as carriers may be a promising choice due to the following advantages: first, environmentally friendly electrolytes; second, nickel-ion electrolytes are lighter than H3O + and NH4 + The electrolyte exhibits a milder acidic environment, which means less corrosiveness and a safer working environment; third, fast kinetic behavior; fourth, Ni 2+ Small ionic radius It not only minimizes the volume change of the host material during the reversible embedding / extraction process, but also facilitates the realization of high-rate performance.
[0005] Prussian Blue Analog (PBA) A 2-x M[Fe(CN)6] 1-y zH2O, where A is an alkali metal and M represents a transition metal, is a very attractive candidate for the positive electrode of rechargeable batteries due to its open channel structure suitable for ion insertion / extraction. In particular, Mn-based PBAs have received close attention in recent years in electrochemical energy storage applications because they have two redox active pairs (Mn 2+ / Mn 3+ and Fe 2+ / Fe 3+), thereby providing high specific capacity and high operating voltage. However, Mn-PBA as a cathode material usually exhibits high polarizability and poor cycle stability due to its poor conductivity, side reactions with the electrolyte, phase change, and dissolution of the Mn element during the cycle. Therefore, exploring a technical solution that can effectively solve the above-mentioned manganese phase change and dissolution problems is an urgent problem to be solved by those skilled in the art. Summary of the invention
[0006] In view of the needs of the prior art, the purpose of the present invention is to provide an application of a high entropy Prussian blue material in the preparation of an aqueous nickel-ion battery. The present invention is based on the application of a high entropy strategy in Prussian blue analogs (PBAs) of Mn, which can lead to a decrease in the spin state of Mn, that is, in a low spin state (t 2g 4 e g 0 ),Mn 3+ The electrons occupy all t 2g energy level, which promotes the stability of the crystal structure and suppresses the activity of JT distortion, which can be attributed to the e g The symmetric occupied state of the orbital, thus, in the aqueous nickel ion storage, the high entropy PBA -1 After 1000 cycles under the conditions of , the retention rate can still exceed 70%, that is, the high entropy Prussian blue positive electrode material prepared by the present invention is beneficial to enhancing the nickel ion diffusion kinetics and comprehensive electrochemical properties of the material, and has broad application prospects in the field of aqueous nickel batteries.
[0007] Specifically, the present invention provides the following technical solutions:
[0008] The first aspect of the present invention provides an application of a high entropy Prussian blue material in the preparation of an aqueous nickel-ion battery, wherein the electrolyte used in the aqueous nickel-ion battery is an aqueous solution of nickel trifluoromethanesulfonate; the high entropy Prussian blue material is used as a positive electrode active material.
[0009] Preferably, the method for preparing the high entropy Prussian blue material comprises the following steps:
[0010] S1, mixing potassium hexacyanoferrate, trisodium citrate and deionized water, and stirring to obtain solution A;
[0011] S2, mixing transition metal salt and deionized water, stirring to obtain solution B;
[0012] S3. Add solution B into solution A for aging reaction to obtain the product.
[0013] Further preferably, in step S1, the mass fractions of the potassium hexacyanoferrate and trisodium citrate are both greater than or equal to 99.5%; the molar ratio of the potassium hexacyanoferrate and trisodium citrate is 1:0.01-100; the stirring time is 2-48 hours, and the speed is 500-1000 rpm.
[0014] Further preferably, in step S2, the anion of the transition metal salt is selected from one or more of sulfate, acetate, hydrochloride and nitrate; the cation of the transition metal salt is selected from one or more of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper and zinc; the stirring time is 2 to 48 hours, and the speed is 500 to 1000 rpm; further preferably, the types of cations used in the transition metal salt are not less than five, and the molar ratio of any two cations is 0.1 to 10.
[0015] Further preferably, in step S3, the temperature of the aging reaction is room temperature, and the time is 2 to 48 hours; the crude product after the aging reaction is washed with deionized water and anhydrous ethanol in sequence, and dried to obtain a high-entropy Prussian blue material; wherein the drying atmosphere is air or vacuum, the drying temperature is 60 to 100°C, and the time is 6 to 24 hours.
[0016] Preferably, the slurry obtained by uniformly mixing the positive electrode active material, the conductive agent and the binder is attached to the current collector substrate as a protective coating; the current collector substrate is selected from one or more of stainless steel foil, aluminum foil, copper foil and carbon paper; further preferably, the current collector substrate is a carbon paper current collector.
[0017] Preferably, the conductive agent is selected from one or more of Ketjen black, conductive carbon black, acetylene black and Super P; further preferably, the conductive agent is Ketjen black.
[0018] Preferably, the binder is selected from one or more of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylonitrile, polyvinyl alcohol, polytetrafluoroethylene, polyvinylidene fluoride and polyimide; further preferably, the binder is polyvinylidene fluoride (PVDF).
[0019] In a second aspect of the present invention, there is provided a positive electrode material for an aqueous nickel-ion battery, the positive electrode material comprising a high entropy Prussian blue material; the positive electrode material comprising a high entropy Prussian blue material;
[0020] The preparation method of the high entropy Prussian blue material comprises the following steps:
[0021] S1, mixing potassium hexacyanoferrate, trisodium citrate and deionized water, and stirring to obtain solution A;
[0022] S2, mixing transition metal salt and deionized water, stirring to obtain solution B;
[0023] S3, adding solution B to solution A for aging reaction, to obtain;
[0024] Among them, the molar ratio of potassium hexacyanoferrate and trisodium citrate is 1:0.01-100; the anion of the transition metal salt is selected from one or more of sulfate, acetate, hydrochloride and nitrate; the cation of the transition metal salt is selected from one or more of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper and zinc; the types of cations used in the transition metal salt are not less than five, and the molar ratio of any two cations is 0.1-10; the temperature of the aging reaction is room temperature, and the time is 2-48 hours; the crude product after the aging reaction is washed with deionized water and anhydrous ethanol in turn, and the high entropy Prussian blue material is obtained after drying.
[0025] Preferably, the positive electrode material further includes a conductive agent and a binder.
[0026] Preferably, the mass ratio of the high entropy Prussian blue material to the conductive agent and the binder is 6 to 10:1 to 2:1, preferably 7:2:1.
[0027] The third aspect of the present invention provides an aqueous nickel-ion battery, comprising the positive electrode material described in the second aspect, and also comprising a negative electrode material, a separator and an electrolyte;
[0028] Wherein, the negative electrode material is nickel foam coated with activated carbon;
[0029] The electrolyte is an aqueous solution, preferably a nickel trifluoromethanesulfonate aqueous solution;
[0030] The diaphragm is glass fiber.
[0031] The beneficial effects achieved by one or more of the above technical solutions of the present invention are as follows:
[0032] (1) The positive electrode material prepared by the present invention is a high-entropy Prussian blue material, which is beneficial to enhancing the nickel ion diffusion kinetics and comprehensive electrochemical performance of the material, and has broad application prospects in the field of aqueous nickel batteries.
[0033] (2) The positive electrode material prepared by the present invention only stores nickel ions during the charge and discharge process and exhibits a relatively high nickel ion diffusion coefficient (1.4×10 -8 cm 2 s -1 ).
[0034] (3) The positive electrode material prepared by the present invention has a high discharge capacity (86 mAh g -1 ), long cycle life (1000 cycles) and other battery characteristics as well as environmental friendliness and low cost practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0036] Figure 1 This is the XRD pattern of the high entropy Prussian blue material synthesized in Example 1 of the present invention;
[0037] Figure 2 TEM images of the high entropy Prussian blue material synthesized in Example 1 of the present invention; wherein (a) is a low-magnification transmission image; (b) is a high-resolution transmission image;
[0038] Figure 3 This is a constant current charge-discharge curve diagram of an aqueous nickel-ion battery using the high-entropy Prussian blue material synthesized in Example 1 of the present invention as a positive electrode active material;
[0039] Figure 4 This is a cycle performance diagram of an aqueous nickel-ion battery using the high-entropy Prussian blue material synthesized in Example 1 of the present invention as a positive electrode active material;
[0040] Figure 5 The constant current intermittent titration method of an aqueous nickel-ion battery using the high entropy Prussian blue material synthesized in Example 1 of the present invention as the positive electrode active material and the calculated nickel ion diffusion coefficient;
[0041] Figure 6 It is a statistical chart of the ionic radius and chemical properties of hydrated ions of different metal ions. DETAILED DESCRIPTION
[0042] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0043] As mentioned above, Mn-PBA as a cathode material usually exhibits high polarizability and poor cycle stability due to its poor conductivity, side reactions with the electrolyte, phase change, and dissolution of the Mn element during the cycle. Therefore, the present invention, by introducing a high-entropy Prussian blue material as a positive electrode material, is conducive to enhancing the nickel ion diffusion kinetics and the comprehensive electrochemical performance of the material, and has broad application prospects in the field of aqueous nickel batteries.
[0044] A first typical embodiment of the present invention provides an application of a high entropy Prussian blue material in the preparation of an aqueous nickel-ion battery, wherein the electrolyte used in the aqueous nickel-ion battery is an aqueous solution of nickel trifluoromethanesulfonate; the high entropy Prussian blue material is used as a positive electrode active material.
[0045] In one or more examples of this embodiment, the method for preparing the high entropy Prussian blue material comprises the following steps:
[0046] S1, mixing potassium hexacyanoferrate, trisodium citrate and deionized water, and stirring to obtain solution A;
[0047] S2, mixing transition metal salt and deionized water, stirring to obtain solution B;
[0048] S3. Add solution B into solution A for aging reaction to obtain the product.
[0049] In one or more examples of this implementation mode, in step S1, the mass fractions of the potassium hexacyanoferrate and trisodium citrate are both greater than or equal to 99.5%; the molar ratio of the potassium hexacyanoferrate and trisodium citrate is 1:0.01-100; the stirring time is 2-48 hours, and the speed is 500-1000 rpm.
[0050] In one or more embodiments of this embodiment, in step S2, the anion of the transition metal salt is selected from one or more of sulfate, acetate, hydrochloride and nitrate; the cation of the transition metal salt is selected from one or more of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper and zinc; the stirring time is 2 to 48 hours, and the speed is 500 to 1000 rpm; further preferably, the types of cations used in the transition metal salt are not less than five, and the molar ratio of any two cations is 0.1 to 10.
[0051] In one or more embodiments of this implementation mode, in step S3, the temperature of the aging reaction is room temperature, and the time is 2 to 48 hours; the crude product after the aging reaction is washed with deionized water and anhydrous ethanol in sequence, and the high entropy Prussian blue material is obtained after drying; wherein the drying atmosphere is air or vacuum, the drying temperature is 60 to 100°C, and the time is 6 to 24 hours.
[0052] In one or more examples of this embodiment, a slurry obtained by uniformly mixing the positive electrode active material, the conductive agent and the binder is attached to a current collector substrate as a protective coating; the current collector substrate is selected from one or more of stainless steel foil, aluminum foil, copper foil and carbon paper; further preferably, the current collector substrate is a carbon paper current collector.
[0053] In one or more examples of this implementation, the conductive agent is selected from one or more of Ketjen black, conductive carbon black, acetylene black and Super P; further preferably, the conductive agent is Ketjen black.
[0054] In one or more examples of this embodiment, the binder is selected from one or more of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylonitrile, polyvinyl alcohol, polytetrafluoroethylene, polyvinylidene fluoride and polyimide; further preferably, the binder is polyvinylidene fluoride (PVDF).
[0055] A second typical embodiment of the present invention provides a positive electrode material for an aqueous nickel-ion battery, wherein the positive electrode material comprises a high entropy Prussian blue material;
[0056] The preparation method of the high entropy Prussian blue material comprises the following steps:
[0057] S1, mixing potassium hexacyanoferrate, trisodium citrate and deionized water, and stirring to obtain solution A;
[0058] S2, mixing transition metal salt and deionized water, stirring to obtain solution B;
[0059] S3, adding solution B to solution A for aging reaction, to obtain;
[0060] Among them, the molar ratio of potassium hexacyanoferrate and trisodium citrate is 1:0.01-100; the anion of the transition metal salt is selected from one or more of sulfate, acetate, hydrochloride and nitrate; the cation of the transition metal salt is selected from one or more of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper and zinc; the types of cations used in the transition metal salt are not less than five, and the molar ratio of any two cations is 0.1-10; the temperature of the aging reaction is room temperature, and the time is 2-48 hours; the crude product after the aging reaction is washed with deionized water and anhydrous ethanol in turn, and the high entropy Prussian blue material is obtained after drying.
[0061] In one or more examples of this implementation, the positive electrode material further includes a conductive agent and a binder.
[0062] In one or more examples of this implementation, the mass ratio of the high entropy Prussian blue material to the conductive agent and the binder is 6 to 10:1 to 2:1, preferably 7:2:1.
[0063] A third typical embodiment of the present invention provides an aqueous nickel-ion battery, comprising the positive electrode material described in the second aspect, and further comprising a negative electrode material, a separator and an electrolyte;
[0064] Wherein, the negative electrode material is nickel foam coated with activated carbon;
[0065] The electrolyte is an aqueous solution, preferably a nickel trifluoromethanesulfonate aqueous solution;
[0066] The diaphragm is glass fiber.
[0067] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0068] Example 1 :This embodiment provides a high entropy Prussian blue material and a preparation method thereof
[0069] (1) Weigh 0.005 mol of chemically pure potassium hexacyanoferrate and 0.01 mol of chemically pure trisodium citrate, add deionized water into a 100 mL beaker and stir to form solution A;
[0070] (2) Weigh 0.002 mol of chemically pure copper chloride, 0.002 mol of chemically pure cobalt chloride, 0.002 mol of chemically pure manganese chloride, 0.002 mol of chemically pure nickel chloride, and 0.002 mol of chemically pure zinc chloride, add deionized water to a 100 mL beaker and mix well to form a solution B, which is added together with the solution A obtained in step (1) into a beaker containing 200 mL of deionized water to form a solution C, and stirred for reaction for 2 hours. After the reaction is completed, the reaction system is aged at room temperature for 24 hours to obtain a brown crude product;
[0071] (3) The brown crude product obtained in step (2) was heated and washed in 50 mL of water and ethanol five times in sequence;
[0072] (4) drying the brown product washed in step (3) in air at 60° C. for 12 hours;
[0073] (5) Grind the dried brown product into powder.
[0074] like Figure 1 As shown, the X-ray diffraction spectrum (XRD) analysis of the high entropy Prussian blue material prepared in this example shows that the obtained HE-PBA has a typical cubic structure.
[0075] like Figure 2 As shown, transmission electron microscopy (TEM) analysis of the high entropy Prussian blue material prepared in this embodiment shows that HE-PBA has a clear nanocubic morphology with a crystal size of about 170 nm. In addition, the high-resolution transmission image shows an ordered lattice with a lattice spacing of 0.37 nm, which can correspond to the (220) plane of HE-PBA.
[0076] Example 2:This embodiment provides a high entropy Prussian blue material and a preparation method thereof
[0077] (1) Weigh 0.005 mol of chemically pure potassium hexacyanoferrate and 0.005 mol of chemically pure trisodium citrate, add deionized water into a 100 mL beaker and stir to form solution A;
[0078] (2) Weigh 0.002 mol of chemically pure vanadium chloride, 0.002 mol of chemically pure cobalt chloride, 0.002 mol of chemically pure manganese chloride, 0.002 mol of chemically pure nickel chloride, and 0.002 mol of chemically pure chromium chloride, add deionized water to a 100 mL beaker and mix well to form a solution B, which is added together with the solution A obtained in step (1) into a beaker containing 200 mL of deionized water to form a solution C, and stirred for reaction for 2 hours. After the reaction is completed, the reaction system is aged at room temperature for 48 hours to obtain a brown crude product;
[0079] (3) The brown crude product obtained in step (2) was heated and washed in 50 mL of water and ethanol five times in sequence;
[0080] (4) drying the brown product washed in step (3) in air at 60° C. for 12 hours;
[0081] (5) Grind the dried brown product into powder.
[0082] Example 3 :This embodiment provides a high entropy Prussian blue material and a preparation method thereof
[0083] (1) Weigh 0.005 mol of chemically pure potassium hexacyanoferrate and 0.015 mol of chemically pure trisodium citrate, add deionized water into a 100 mL beaker and stir to form solution A;
[0084] (2) Weigh 0.002 mol of chemically pure vanadium chloride, 0.002 mol of chemically pure scandium chloride, 0.002 mol of chemically pure manganese chloride, 0.002 mol of chemically pure gallium chloride, and 0.002 mol of chemically pure chromium chloride, add deionized water to a 100 mL beaker and mix well to form a solution B, which is added together with the solution A obtained in step (1) into a beaker containing 200 mL of deionized water to form a solution C, and stirred for reaction for 10 hours. After the reaction is completed, the reaction system is aged at room temperature for 24 hours to obtain a brown crude product;
[0085] (3) The brown crude product obtained in step (2) was heated and washed in 50 mL of water and ethanol five times in sequence;
[0086] (4) drying the brown product washed in step (3) in air at 80° C. for 12 h;
[0087] (5) Grind the dried brown product into powder.
[0088] Application Example 1 :This application example provides an aqueous nickel-ion battery and its electrochemical performance test
[0089] An aqueous secondary nickel-ion battery, wherein the positive electrode material is the high-entropy Prussian blue material described in Example 1. The positive electrode material, the conductive agent Ketjen black, and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 7:2:1 are weighed, N-methylpyrrolidone (NMP) is added and stirred for 10 hours to form a uniform slurry, and the slurry is coated on a carbon paper current collector with a surface density of about 2 mg cm -2 , dried in a vacuum drying oven at 60°C for 12 h, cooled to room temperature and cut into round electrodes with a diameter of 10 mm.
[0090] The above circular electrode piece was used as the positive electrode, the nickel foam coated with activated carbon with a diameter of 10 mm was used as the negative electrode, the glass fiber was used as the separator, and the 2 mol / L nickel trifluoromethanesulfonate aqueous solution was used as the electrolyte to assemble a 2032 button battery.
[0091] Electrochemical performance test:
[0092] like Figure 3 As shown in the constant current charge-discharge curve, the discharge voltage platform of HE-PBA is 0.78 V, and the initial discharge specific capacity is 86 mAh g -1 ;
[0093] like Figure 4 As shown, the aqueous nickel-ion battery based on high entropy Prussian blue cathode material is -1 86 mAh g -1 Discharge capacity, 1000 cycle life;
[0094] like Figure 5 As shown, the nickel ion diffusion coefficient D is 1.4×10 -8 cm 2 s -1 .
[0095] Application Example 2 :This application example provides a performance comparison between aqueous ion batteries
[0096] Experimental process: In a 2032 button cell, half-cell electrochemical measurements were performed using LiOtf, NaOtf, NH4Otf, Zn(Otf)2, Mg(Otf)2, Ca(Otf)2, Mn(Otf)2, and Al(Otf)3 solutions. Acetylene black and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 7:2:1, 1-methyl-2-pyridone (NMP) was added, coated on carbon paper, and vacuum dried at 80°C for 12 hours. Carbon paper was used as the current collector for the working electrode.
[0097] The results are as follows Figure 6 As shown, although the radius of the solvated nickel ions of the aqueous nickel ions prepared by the present invention is relatively large, during the process of embedding into the positive electrode material, after the ions are desolvated, the radius of the divalent nickel ions is the smallest (0.069nm), and is even smaller than the radius of the lithium ions (0.076nm). Therefore, more nickel ions will be embedded in the Prussian blue positive electrode material, thereby obtaining a higher volumetric specific capacity.
[0098] Specifically, aqueous nickel-ion batteries based on high-entropy Prussian blue cathode materials can achieve 8133mAh cm -3 The volumetric capacity is much higher than that of aqueous lithium-ion batteries assembled with high-entropy Prussian blue cathode materials (2062 mAh cm -3 ), aqueous sodium-ion batteries (1128 mAh cm -3 ), aqueous potassium ion battery (591mAh cm -3 ), aqueous zinc-ion batteries (5851mAh cm -3 ), aqueous magnesium ion battery (3883mAh cm -3 ) and aqueous calcium ion batteries (2073mAh cm -3 ).
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. Application of a high entropy Prussian blue material in the preparation of an aqueous nickel-ion battery, characterized in that: The electrolyte used in the aqueous nickel-ion battery is a nickel trifluoromethanesulfonate aqueous solution; the high entropy Prussian blue material is used as a positive electrode active material.
2. The use according to claim 1, characterized in that The preparation method of the high entropy Prussian blue material comprises the following steps: S1, mixing potassium hexacyanoferrate, trisodium citrate and deionized water, and stirring to obtain solution A; S2, mixing transition metal salt and deionized water, stirring to obtain solution B; S3. Add solution B into solution A for aging reaction to obtain the product.
3. The use according to claim 2, characterized in that In step S1, the mass fractions of the potassium hexacyanoferrate and trisodium citrate are both greater than or equal to 99.5%; the molar ratio of the potassium hexacyanoferrate and trisodium citrate is 1:0.01-100; the stirring time is 2-48 hours, and the speed is 500-1000 rpm.
4. The use according to claim 2, characterized in that In step S2, the anion of the transition metal salt is selected from one or more of sulfate, acetate, hydrochloride and nitrate; the cation of the transition metal salt is selected from one or more of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper and zinc; the stirring time is 2 to 48 hours, and the speed is 500 to 1000 rpm; preferably, the types of cations used in the transition metal salt are not less than five, and the molar ratio of any two cations is 0.1 to 10.
5. The use according to claim 2, characterized in that In step S3, the temperature of the aging reaction is room temperature, and the time is 2 to 48 hours; the crude product after the aging reaction is washed with deionized water and anhydrous ethanol in sequence, and the high entropy Prussian blue material is obtained after drying; wherein the drying atmosphere is air or vacuum, the drying temperature is 60 to 100° C., and the time is 6 to 24 hours.
6. The use according to claim 1, characterized in that The slurry obtained by uniformly mixing the positive electrode active material, the conductive agent and the binder is attached to the current collector substrate as a protective coating; the current collector substrate is selected from one or more of stainless steel foil, aluminum foil, copper foil and carbon paper; preferably, the current collector substrate is a carbon paper current collector.
7. The use according to claim 6, characterized in that The conductive agent is selected from one or more of Ketjen black, conductive carbon black, acetylene black and Super P; preferably, the conductive agent is Ketjen black; The binder is selected from one or more of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylonitrile, polyvinyl alcohol, polytetrafluoroethylene, polyvinylidene fluoride and polyimide; preferably, the binder is polyvinylidene fluoride.
8. A positive electrode material for an aqueous nickel-ion battery, characterized in that: The positive electrode material includes a high entropy Prussian blue material; The preparation method of the high entropy Prussian blue material comprises the following steps: S1, mixing potassium hexacyanoferrate, trisodium citrate and deionized water, and stirring to obtain solution A; S2, mixing transition metal salt and deionized water, stirring to obtain solution B; S3, adding solution B to solution A for aging reaction, to obtain; Among them, the molar ratio of potassium hexacyanoferrate and trisodium citrate is 1:0.01-100; the anion of the transition metal salt is selected from one or more of sulfate, acetate, hydrochloride and nitrate; the cation of the transition metal salt is selected from one or more of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper and zinc; the types of cations used in the transition metal salt are not less than five, and the molar ratio of any two cations is 0.1-10; the temperature of the aging reaction is room temperature, and the time is 2-48 hours; the crude product after the aging reaction is washed with deionized water and anhydrous ethanol in turn, and the high entropy Prussian blue material is obtained after drying.
9. The positive electrode material according to claim 8, characterized in that The positive electrode material also includes a conductive agent and a binder; preferably, the mass ratio of the high entropy Prussian blue material to the conductive agent and the binder is 6 to 10:1 to 2:1, preferably 7:2:
1.
10. An aqueous nickel-ion battery comprising the positive electrode material according to claim 8 or 9, and further comprising a negative electrode material, a separator and an electrolyte; in, The negative electrode material is nickel foam coated with activated carbon; The electrolyte is an aqueous solution, preferably a nickel trifluoromethanesulfonate aqueous solution; The diaphragm is glass fiber.